2021
DOI: 10.3390/jpm11090830
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Tertiary Prevention in Patients with Primary Open Angle Glaucoma

Abstract: The purpose of the study is to assess the health of patients in the activity of tertiary prevention dedicated to preventing blindness caused by POAG (primary glaucoma with open angle and high tension) and NTG (primary glaucoma with open-angle and statistically normal tension—particular form of glaucoma with open angle) and preservation of the remaining visual function. The design of the study is epidemiological, observational, descriptive and retrospective, and uses only the data recorded in the existing recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Several reports have shown that intestinal dysbiosis and a decrease in short-chain fatty acid-producing bacteria increase the risk of type 2 diabetes mellitus ( 13 , 41 ). According to the results of this MR study, we can implement secondary prevention for people exposed to T2DM risk factors ( 42 ). Specifically, we can carry out targeted screening of intestinal flora in people exposed to T2DM risk factors, such as the elderly or obese people, in order to detect diseases early and establish treatment mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that intestinal dysbiosis and a decrease in short-chain fatty acid-producing bacteria increase the risk of type 2 diabetes mellitus ( 13 , 41 ). According to the results of this MR study, we can implement secondary prevention for people exposed to T2DM risk factors ( 42 ). Specifically, we can carry out targeted screening of intestinal flora in people exposed to T2DM risk factors, such as the elderly or obese people, in order to detect diseases early and establish treatment mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Our study may provide preliminary findings for the prevention of DM. Secondary prevention is a method of identifying the illness by means of targeted screening measures and routine medical monitoring ( 44 ). The American Diabetes Association (ADA) highlights the significance of screening for diabetes, as diabetes often lacks recognizable symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of efficient screening initiatives, individuals with high risk are less likely to undertake the essential intervention to prevent or delay the progression to T2D ( 45 ). Tertiary prevention refers to the measures aimed at individuals who have already experienced disease or injury, with the goal of mitigating the consequences of the condition, slowing down disease progression, and enhancing quality of life ( 44 ). The majority of medications designed to delay the onset of diabetes are associated with considerable expenses, while a substantial portion remains uncovered by insurance providers due to the lack of an approved indication by the Food and Drug Administration (FDA) ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Visual field testing, supplemented with new techniques, provides information that can detect disease progression and improves clinical decision-making, being useful for monitoring patients and reducing the burden of disease [ 36 ]. Elevated IOP values in patients with suspected OHT justify hypotensive treatment [ 37 ]. Delaying treatment in OHT can lead to a significant increase in the incidence of POAG, noting that the cumulative proportion of POAG development after 13 years is 0.22 in the untreated cohort (with a 7.5-year treatment delay) compared to 0.16 in the treated cohort [ 38 ].…”
Section: Discussionmentioning
confidence: 99%